2020
DOI: 10.1590/2175-7860202071061
|View full text |Cite
|
Sign up to set email alerts
|

Ethnopharmacology: a laboratory science?

Abstract: In 1962, Richard Evans Schultes defined ethnobotany as “the study of the relationships which exist between people of the primitive society and their plant environment”. Ethnopharmacology, considered a sub-discipline of ethnobotany, has been conceptualized in different ways over time. Since the 80’s, implicit in these different concepts was the need for the validation of traditional/popular knowledge through pharmacological and phytochemical studies. According to these ideas, plants or animals identified during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(14 reference statements)
1
1
0
Order By: Relevance
“…The study revealed that the ethnobotanical knowledge of local shepherds and animal caretakers was quite consistent with the nutritional data of studied grasses. The current findings are in agreement with the reported data of Keba et al 10 , Dhungana et al 11 , Talore 12 , Rakib-Uz-Zaman et al 90 and Rodrigues et al 91 who supported the positive association between laboratory results and ethnobotanical knowledge. Therefore, traditional knowledge should not be ignored and must be used as an approach for better understanding of nutritive potential of local fodder/forage resources under predominant environmental conditions.…”
Section: Discussionsupporting
confidence: 93%
“…The study revealed that the ethnobotanical knowledge of local shepherds and animal caretakers was quite consistent with the nutritional data of studied grasses. The current findings are in agreement with the reported data of Keba et al 10 , Dhungana et al 11 , Talore 12 , Rakib-Uz-Zaman et al 90 and Rodrigues et al 91 who supported the positive association between laboratory results and ethnobotanical knowledge. Therefore, traditional knowledge should not be ignored and must be used as an approach for better understanding of nutritive potential of local fodder/forage resources under predominant environmental conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Despite advances, an issue still remains in several decision-making and research forums: how ethical is it to use a knowledge system (with its values and methods of construction and transmission of knowledge) to validate another knowledge system (with other values and methods)? For example, most of the contemporary concepts attributed to ethnopharmacology concern the validation of the use of biotic elements by biomedicine, which from the epistemological point of view is mistaken if we consider the other areas of ethnosciences (Rodrigues & Oliveira 2020). Validation itself can be called into question when the hegemonic character of academic science is recognized (Carneiro da Cunha 2009) because there is not a single method or a single science.…”
Section: Ethnoecology In Contextmentioning
confidence: 99%